Calculation method for the interface contact stress of steel tube-to-sleeve grouted connections subjected to bending moments. (May 2023) - Wang, Zhanwen; Chen, Jianwei; Zhang, Rui
Abstract: Steel tube-to-sleeve grouted connections (GCs) have been widely used for offshore wind turbine structures due to its excellent structural behaviour. Interfacial contact stress is a crucial indicator for evaluating the ultimate stress state of the GCs. However, the information is still limited regarding the calculation formulas for contact stresses considering the effects of friction coefficient, elastic modulus of grout, and cross-sectional dimensions of steel tube and sleeve. An extensive FE analysis on a total of twenty full-scale grouted connection specimens under bending moments was performed in this paper. Based on the parametric analysis results, the contact stress distribution pattern was obtained and the design formulas were derived for calculating the contact stress. In these formulas, the cross-sectional influence factor (CIF) is proposed to evaluate the effect of cross-sectional dimensions of steel tube and sleeve. The proposed formulas were featured with a reasonable accuracy and could be adopted in the flexural design of GCs.